Meningkatkan Hasil Belajar Siswa SDN 25 Talamau Kelas VI pada Mata Pelajaran PAI dengan Pembelajaran Berbasis Problem Solving - Ratih Afifania; Yosi Astaria (Kampus Akademik Publiser, 2024)
This research is a classroom action research (CAR) motivated by problems that emerged in Islamic Religious Education (PAI) subjects in sixth-grade students at SDN 25 Talamau. These problems include a monotonous learning environment, students' lack of enthusiasm for PAI lessons, and suboptimal learning outcomes. The cause is the learning process, which is still dominated by lecture methods. The chosen corrective action is the use of problem solving learning methods. The subjects of this study were 31 sixth grade students of SDN 25 Talamau. Data collection techniques used observation, interviews, tests and documentation. The data analysis techniques used were qualitative descriptive approach and descriptive statistics. This classroom action research was conducted in two cycles, with the results of the study stating that (1) the implementation of the problem solving learning model in Islamic Religious Education subjects had a positive impact on student learning outcomes (2) these indicators can be seen from the increase in student learning outcomes after the application of the problem solving model, students were more enthusiastic and enthusiastic in participating in Islamic Religious Education lessons, educational interactions between teachers and students took place well accompanied by an optimal increase in academic abilities in Islamic Religious Education subjects. The increase in student learning activities can be seen from the increase in percentage in cycle I of 61.29% then increased in cycle II by 93.54%. Thus, this study is considered successful in improving student learning outcomes through the application of problem solving methods.